Pengaruh Lingkungan Kerja Fisik Terhadap Kinerja Pegawai di Kantor Kecamatan Kulo Kabupaten Sidenreng Rappang - Fitriani, Fitriani; Adnan, A. Astinah (Universitas Gajah Putih, 2025)
This study aims to determine the influence of the physical work environment on employee performance in the Kulo sub-district office, Sidenreng Rappang Regency. The population in this study is 31 employees who work in the kulo sub-district office. This study uses a quantitative method and uses two types of variables, namely the physical work environment (X) and employee performance (Y). The sampling technique is a saturated sampling technique of 31 people. The data collection techniques used in this study are observation, questionnaire and literature study. Using the help of the IBM SPSS statistics 21.0 application. The results of this study show that the physical work environment variable (X) with a recapitulation result of 67% is categorized as good. Therefore, the physical work environment must be improved again. The performance of the employee (Y) with the achievement of the respondent is 50%, so that the value of t is calculated > t table, or 5.580 > 2.045, then Ho is rejected and Ha is accepted, meaning significant. So the influence of the physical work environment has a significant effect on the performance of employees at the Kulo sub-district office, Sidenreng Rappang Regency.